Interface Engineering by Thiazolium Iodide Passivation Towards Reduced Thermal Diffusion and Performance Improvement in Perovskite Solar Cells. (11th February 2020) - Salado, Manuel; Andresini, Michael; Huang, Peng; Khan, Mohd Taukeer; Ciriaco, Fulvio; Kazim, Samrana; Ahmad, Shahzada
Abstract: Interface engineering has become one of the most facile and effective approaches to improve solar cells performance and its long‐term stability and to retard unwanted side reactions. Three passivating agents are developed which can functionalize the surface and induce hydrophobicity, by employing substituted thiazolium iodide (TMI) for perovskite solar cells fabrication. The role of TMI interfacial layers in microstructure and electro‐optical properties is assessed for structural as well as transient absorption measurements. TMI treatment resulted in V OC and fill factor enhancement by reducing possible recombination paths at the perovskite/hole selective interface and by reducing the shallow as well as deep traps. These in turn allow to achieve higher performance as compared to the pristine surface. Additionally, the TMI passivated perovskite layer considerably reduces CH3 NH3 + thermal diffusion and degradation induced by humidity. The un‐encapsulated perovskite solar cells employing TMI exhibit a remarkable stability under moisture levels (≈50% RH), retaining ≈95% of the initial photon current efficiency after 800 h of fabrication, paving the way towards a potential scalable endeavor. Abstract : The thiazolium iodide‐passivated perovskite layer reduces CH3 NH3 + thermal diffusion and shallow as well as deep traps, which in turn yield improved performance.